Nisina como conservante de alimentos : revisión sistemática de la literatura (2015)
ABSTRACT: Currently, one of the mostimportant obligations of the food industry is to be able to guarantee product innocuousness, which translates into a need for preservatives. Nisin, an antimicrobial peptide produced by Lactococcus lactis, holds the greatest potential as a natural preservative used in food matrices. Nisin is the only bacteriocin that has been approved by the WHO to be used as a preservative in the food industry. Objective: This review aims at describing the use of nisin as an antimicrobial in different dietary matrices. Methods: A systematic search of the literature was performed in Science Direct, Scopus and Springer. The search path was adjusted according to the algorithm of each database. After the evaluation of the various inclusion and exclusion criteria, the search resulted in a total of 41 articles published between 2007 and 2017. Results and conclusion: In most dietary matrices evaluated - cheeses, milk, meat, and wines, among others - it was possible to prove the effective elimination of pathogenic microorganisms with nisin and its contribution to the biopreservation of foods. Nisin helps extend the useful life of these products without altering its sensory characteristics.